PENERAPAN KEDISIPLINAN KERJA SISWA KELAS IX DALAM KEGIATAN PRAKTIK MATA PELAJARAN TATA HIDANG DI SEKOLAH MENENGAH KEJURUAN - Herlina Marita Budiarti (KELUARGA: Jurnal Ilmiah Pendidikan Kesejahteraan Keluarga, 2019)
The purpose of this study is to describe understanding, the application of discipline in practice activities in the Vocational High School and the supporting factors and obstacles faced. The method in this study uses qualitative descriptive. Data were obtained from interviews, observations, and documentation with deputy principal informants, Hospice teachers, students one, students two, and students three. Validity of data with triangulation techniques. The technique of analyzing data through data collection steps, data reduction, data display, conclusion drawing. The results of the study show that: 1) Students' understanding of the application of discipline in practice is good. 2) Implementation of discipline in practical learning is good, but for fear of being disciplined has not become part of every student's life. 3) Supporting and inhibiting factors in implementing discipline: students who are disciplined discipline, uphold honesty, responsibility and students are still difficult to manage but not all are just a few.